Factors Associated with the Behavior of Food Handlers in the Application of Good Manufacturing Practice (GMP) in the Household Food Industry (HFI) in Karangasem Regency - Ni Made Astini Handayani; Kadek Tresna Adhi; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2015)
Backgrounds and purpose: Indonesia is considered of the countries in Southeast Asia with low food quality. The poor behaviors of food handlers in applying good manufacturing practice may bring about a decline in food quality which can lead to the risk of health conditions such as diarrhea, worm infection or food poisoning. This study aims to determine the factors associated with the behaviors of food handlers in the application of good manufacturing practice at the household food industry level. Methods: Cross-sectional survey was conducted among 79 food handlers, working at the household food industry in Karangasem. Data were collected through interviews and observations and analyzed using poisson regression to understand the association of knowledge, attitudes and managerial support with behavior of food handlers. Results: The knowledge and attitude of food handlers were relatively poor at respectively 48.10% and 53.16%. The behavior of food handlers classified as good was 49.37%. Behavior of food handlers was significantly associated with knowledge (PR=1.48; 95%CI: 1.01-2.15), attitude (PR=2.13; 95%CI: 1.47-3.08) and managerial support (PR=3.01; 95%CI: 1.77-5.13). Conclusion: The behavior of food handlers in the application of good manufacturing practice at the household food industry remains low and was associated with knowledge, attitude and level of managerial support.